Óleo de linhaça e óleo essencial da folha de cravo na alimentação de zebrafish - Silva, Thibério Carvalho da (2017)
Objective the present study was to evaluate the effects of linseed oil (LO) and clove leaf essential oil (CLEO) on zebrafish diet, on dietary antioxidant activity, growth, incorporation, in vivo antioxidant markers and gene expression. Six extruded diets were prepared, isonitrogenous (45% protein) e isocaloric (3969 kcal kg-1), containing the combination of three levels of linseed oil (3, 6 e 9%) with two levels (0.5 e 1%), beyond control diet (without OL and CLEO). A total of 420 zebrafish were used at the age of 40 days post hatching, with an average weight of 0.29 ± 0.04 g. and 30.67 ± 0.71 mm total length. Animals were distributed in glass tanks with a capacity of 50 liters. The experimental design was completely randomized with three replicates in a 3x2 factorial scheme with an additional treatment. Diets containing 1% of CLEO had higher antioxidant activity (p<0.05) with an average increase of 270% compared to control diet. There was no mortality during the experimental period. The final weight and weight gain increased with OL inclusion (isolated effect, p <0.05). Regarding the fatty acid profile in muscle, there was no difference in the sum of saturated fatty acids. Monounsaturated fatty acids increased with OL levels (isolated effect, p <0.05) and polyunsaturated fatty acids of the n-3 series increased with OL and OEFC levels (interaction effect p <0.05). Activity of superoxide dismutase (SOD) and catalase (CAT) reduced with isolated effect for OL and for both factors, respectively. The content of glutathione was lower in the 0.5% OEFC treatment in combination with OL. Lipid peroxidation was lower in the 0.5% OEFC treatment (isolated effect, p <0.05). PPAR-? and SREBP-2 genes showed interaction between the factors (p <0.05) and both showed the same behavior. The treatments with 9 and 0.5% of OL and OEFC were superior to the others. It is recommended to use combined 9% of OL with 0.5% of OEFC for zebrafish